Qualitative data collection tools : design, development, and applications - Billups, Felice D. (Thousand Oaks Sage, 2021)
Qualitative Data Collection Tools: Design, Development, and Applications is a new and unique supplementary text that will guide students and new researchers to design, develop, pilot, and employ qualitative tools in order to collect qualitative data. An often-omitted subject in general qualitative textbooks, qualitative tools form the backbone of the data collection process. Students and new researchers are frequently left to create their own qualitative tools from scratch, an unnecessary hurdle in the qualitative research design process. Author Felice D. Billups has used her experience as a qualitative researcher, and in teaching and advising students about qualitative research, to develop the templates in this book as a starting point for readers conducting original qualitative research. The author briefly describes each method of data collection and offers readers suggestions for using and adapting the qualitative instrument templates within the text. Templates of interview protocols, focus group moderator guides, content analysis tools, document analysis tools, reflective questionnaires, diary and journal logs, and observational rubrics give the reader either a cut-and-paste solution for their own research or a starting point to design their own personalized qualitative tools.
The qualitative data collection cycle -- Using the research question to guide qualitative data collection tool design -- Conducting the qualitative study : researcher role, access, trustworthiness, and ethical concerns -- Interview protocols -- Conversational and discourse analysis tools -- Focus group moderator guides -- Observation tools -- Document and artifact analysis tools -- Reflective practice tools -- Synthesis : the qualitative story -- Appendices: a case study of Department X.
Includes bibliographical references (pages 193-204) and index.
Keywords: Qualitative research -- Methodology; Qualitative research -- Methodology